Modelling the Egyptian Shadow Economy: A Currency Demand and A MIMIC Model Approach - Mai Hassan; Friedrich Schneider (Center for Economic Studies and ifo Institute (CESifo), 2016)
We estimate the size and trend of the Egyptian shadow economy using two of the most common methods: the currency demand approach and the structural equation MIMIC model. To the best of our knowledge, this is the first comprehensive study to estimate the size of the shadow economy in Egypt during the last four decades (1976 to 2013). In addition to the standard explanatory variables used in the currency demand approach and MIMIC model, we consider variables that are specifically related to the Egyptian economy such as self-employment, agricultural importance and a proxy for institutional quality of democratic institutions. Our results indicate a decreasing trend of the size of the shadow economy from more than 50% in 1976 to 32% in 2013, yet it still comprises a large portion of the official GDP.
Keywords: C32; H26; I20; O17; P48; 330; shadow economy of Egypt; currency demand approach (CDA); MIMIC estimation